Leveraging Local and Global EdTech Ecosystems to Strengthen Digital Literacy and Learning: A Systematic Review and Meta-Analysis - Bambang Afriadi (Jurnal Evaluasi Pendidikan, 2026)
Background: Educational technology (EdTech) is commonly evaluated through adoption, access, or platform use, although these indicators do not establish digital-literacy development or improved learning. Evidence is also fragmented between locally contextualized platforms, globally scaled services, critical governance research, and intervention studies. Objective: This study synthesized how local or national and global EdTech ecosystems support digital literacy and learning, with particular attention to Indonesia, Malaysia, and Thailand, and quantitatively examined whether hardware- and software-focused interventions differed in their association with learning outcomes in low- and middle-income settings. Methods: A three-layer evidence synthesis was conducted in accordance with PRISMA 2020 principles. A supplied Scopus corpus of 78 records published from 2020 to 4 August 2026 was screened alongside 23 sources from the revised source manuscript and 15 intervention reports identified through citation chasing. Ninety-eight records were retained in the systematic evidence map, 38 sources informed the critical full-text or authoritative-source synthesis, and 30 hardware/software effect-size contrasts from 13 unique reports were included in a secondary random-effects meta-analysis. Effects were aggregated within publication using generalized least squares with an assumed within-publication correlation of 0.50, then pooled using restricted maximum likelihood and modified Hartung-Knapp intervals. Results: The qualitative evidence consistently supported a conditional hybrid-ecology model: local platforms contributed curricular, linguistic, and cultural alignment, while global platforms expanded content, authoring, interoperability, and collaboration. Digital-literacy gains depended on purposeful tasks, teacher competence, equitable access, accessibility, institutional support, and data governance. At publication level, hardware-focused interventions produced a near-zero pooled effect (d = -0.055, 95% CI -0.251 to 0.141; I² = 94.2%), whereas software-focused interventions showed a positive but imprecise effect (d = 0.217, 95% CI -0.024 to 0.458; I² = 90.7%). The modality difference was not definitive in meta-regression (p = 0.096). Contrast-level sensitivity analysis favored software (d = 0.245, 95% CI 0.092 to 0.397), but this estimate was less conservative because correlated outcomes were treated as independent. Conclusions: EdTech contributes through mediated practices rather than technological presence. The convergent evidence favors investment in pedagogically integrated software, teacher capacity, accessibility, and governance over hardware distribution alone. Because the quantitative evidence was highly heterogeneous, secondary, and indirect for digital literacy, the pooled estimates should be interpreted as directional rather than causal.